Dilemmatic Position of State Civil Apparatus (ASN): Maintaining Neutrality or Being Taken by Power - Saepudin Saepudin; Dana Pratiwi (Journal of Government and Political Issues, 2022)
This article investigates the dilemma faced by the ASN in maintaining neutrality amidst political dynamics, particularly during regional head elections (Pilkada) in Indonesia. The study explores the ASN's susceptibility to being exploited for electoral purposes and evaluates how they maintain neutrality according to laws and regulations. Additionally, the article discusses the challenges ASN faces in adhering to the principle of neutrality and potential solutions to these problems. By examining data from the State Civil Apparatus Commission (KASN) and the Election Supervisory Body (Bawaslu) concerning violations of ASN neutrality, the study identifies factors that contribute to ASN involvement in local political contests and the resulting neutrality breaches. The study also underscores the worrisome situation concerning the integrity and neutrality of Indonesia's ASN in fulfilling their duties and responsibilities. The three identified phenomena—position buying and selling, instant career pursuit, and kinship culture or spoil system—indicate political intervention in bureaucracy, resulting in the appointment of incompetent individuals and reduced public service quality. The concerning situation regarding ASN's integrity and neutrality highlights the need for further efforts in implementing bureaucratic reform and strengthening the merit system in Indonesia.